2021
DOI: 10.5863/1551-6776-26.7.669
|View full text |Cite
|
Sign up to set email alerts
|

Peanut (Arachis hypogaea) Allergen Powder-dnfp: The First FDA-approved Oral Immunotherapy for Desensitization of Peanut Allergy in Children

Abstract: Peanut (Arachis hypogaea) Allergen Powder-dnfp (Palforzia, Aimmune™ Therapeutics, Inc.; Brisbane, CA) is the first FDA-approved oral immunotherapy indicated for the mitigation of allergic reactions, including anaphylaxis, in patients with peanut allergy. It may be initiated in individuals 4 to 17 years of age and continued for maintenance in those 4 years of age and older. Initiation and dose titration require a stepwise approach and the supervision of a health care professional. Patients taking Peanut (Arachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Given this circumstance, the use of sFcεRI as a stand-alone biomarker might be limited, but could, maybe together with other factors, give a clearer picture of the allergic status of a patient and might be of use as a follow up marker during tolerance induction, for example, with the newly developed oral immunotherapy for peanut sensitized children. 47 This project was set out as an exploratory study with low patient numbers and a retrospective cross-sectional single center study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this circumstance, the use of sFcεRI as a stand-alone biomarker might be limited, but could, maybe together with other factors, give a clearer picture of the allergic status of a patient and might be of use as a follow up marker during tolerance induction, for example, with the newly developed oral immunotherapy for peanut sensitized children. 47 This project was set out as an exploratory study with low patient numbers and a retrospective cross-sectional single center study design.…”
Section: Discussionmentioning
confidence: 99%
“…As third pathophysiological possibility, also, both mechanisms could be present in food allergic patients depending on the atopic background and the status of the allergy. Given this circumstance, the use of sFcεRI as a stand‐alone biomarker might be limited, but could, maybe together with other factors, give a clearer picture of the allergic status of a patient and might be of use as a follow up marker during tolerance induction, for example, with the newly developed oral immunotherapy for peanut sensitized children 47 …”
Section: Discussionmentioning
confidence: 99%
“…While allergies to cow's milk or chicken egg proteins may resolve naturally during adolescence, allergy to peanut frequently persists into adulthood ( 88 ). Physical or chemical processes can be employed to reduce the allergenicity of peanuts and peanut products, however, avoidance or allergen immunotherapy [e.g., oral immunotherapy, Palforzia ( 89 )] are recommended for sensitized individuals ( 90 , 91 ). Several major peanut allergens have been identified including glycoprotein Ara h 2, which is recognized by IgE antibodies in more than 90% of peanut-allergic individuals ( 92 , 93 ).…”
Section: Crispr Gene Editing Of Allergensmentioning
confidence: 99%
“…This study demonstrated that consistent OIT treatment with PP could lead to decreased sensitivity to peanut allergen exposure. This led to the US Food and Drug Administration (FDA) approval of the first peanut- derived OIT treatment: Palforzia [57]. With the adoption of the first and only FDA-approved PP in the USA for OIT treatment, Palforzia will next become available for treatment in the UK.…”
Section: Immunotherapymentioning
confidence: 99%